Data needs to be a priority - Halford, Alexa J.; Chen, Thomas Y.; Rastaetter, Lutz (Frontiers in Physics, 2022)
Findability, Accessibility, Interoperability, and Reusability (FAIR) data are essential to heliophysics and all scientific research. The principles of FAIR data ensure the reusability and findability of data, as well as its long-term care. The goal is that data are accessible for the ongoing discovery and verification process and can be used on their own or with newly generated data in future studies leading to innovations. With the onset in the previous decades of NASA and other agencies requiring mission data to be open to the public, heliophysics has already made great strides toward FAIR data and benefited from these efforts. Continued improvements in our metadata, data archives, and data portals and the addition of DOIs for data citation will ensure data will be FAIR, enabling further scientific discoveries, reproducibility of results, longitudinal studies, and verification and validation of models. Currently, not all the data collected are findable and on open networks or archives, and not all data on archives have DOIs. Within this study, we make recommendations to prioritize resources needed to satisfy FAIR data principles, treating them as a fundamental research infrastructure rather than a simple research product.• Data collection, preparation, archiving, and accessibility need to be a priority.• Data collection, preparation, archiving, and accessibility need dedicated and sustained funding support.• Data need to be accessible through investment in infrastructure: tools to access and read the data and personnel to maintain these data and IT infrastructure.• Data need to be collected in sustained ways to enable further science and, specifically, model validation efforts.